Understanding the molecular regulation of flavonoid 3’-hydroxylase in anthocyanin synthesis: insights from purple qingke - Lupeng Chen; Youhua Yao; Yongmei Cui; Xin Li; Likun An; Yixiong Bai; Xiaohua Yao; Kunlun Wu (BMC Genomics, 2024)
Abstract Background The Flavonoid 3’-hydroxylase gene(F3’H) is an important structural gene in the anthocyanin synthesis pathway of plants, which has been proven to be involved in the color formation of organs such as leaves, flowers, and fruits in many plants. However, the mechanism and function in barley are still unclear. Results In order to explore the molecular mechanism of the grain color formation of purple qingke, we used the cultivated qingke variety Nierumzha (purple grain) and the selected qingke variety Kunlun 10 (white grain) to conduct transcriptomic sequencing at the early milk, late milk and soft dough stage. Weighted Gene Co-expression Network Analysis (WGCNA) was used to construct weighted gene co-expression network related to grain color formation, and three key modules (brown, yellow, and turquoise modules) related to purple grain of qingke were selected. F3’H (HORVU1Hr1G094880) was selected from the hub gene of the module for the yeast library, yeast two-hybrid (Y2H), subcellular localization and other studies. It was found that in purple qingke, HvnF3’H mainly distributed in the cytoplasm and cell membrane and interacted with several stress proteins such as methyltransferase protein and zinc finger protein. Conclusions The results of this study provide reference for the regulation mechanism of anthocyanin-related genes in purple grain qingke.